2019
DOI: 10.31246/nutriweb-2018-0023
|View full text |Cite
|
Sign up to set email alerts
|

Changes in energy and nutrient intakes among Malaysian adults: findings from the Malaysian Adult Nutrition Survey (MANS) 2003 and 2014

Abstract: Introduction: Monitoring changes in energy and nutrient intakes of the population over the course of time is essential to help healthcare providers develop effective dietary policies. The aim of this study was to assess the changes in the nutrient intake and Recommended Nutrient Intake (RNI) achievements by using the data obtained from the Malaysian Adult Nutrition Surveys (MANS) that were carried out in 2003 and 2014. Mis-reporting of energy intake was taken into account. Methods: Dietary data were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…In contrast to the smaller decline and levelling off in Malaysia's aggregate RCPC, household nutritional surveys suggest that the rice share of consumption is falling (Goh et al 2020). These surveys also suggest a slight increase in average daily rice consumption (from 210 to 250 grams) for those that eat rice and exclusively among men (Kasim et al 2018). There has been a significant decrease in both the population of men (around 5 percent) and women (10 percent) reporting rice consumption (down from 96-97 percent), suggesting that the overall RCPC inclusive of non-eaters may have fallen.…”
Section: Rice Consumption and Developmentmentioning
confidence: 84%
“…In contrast to the smaller decline and levelling off in Malaysia's aggregate RCPC, household nutritional surveys suggest that the rice share of consumption is falling (Goh et al 2020). These surveys also suggest a slight increase in average daily rice consumption (from 210 to 250 grams) for those that eat rice and exclusively among men (Kasim et al 2018). There has been a significant decrease in both the population of men (around 5 percent) and women (10 percent) reporting rice consumption (down from 96-97 percent), suggesting that the overall RCPC inclusive of non-eaters may have fallen.…”
Section: Rice Consumption and Developmentmentioning
confidence: 84%
“…Fish and rice were at one point the traditional staples of Malaysia and the neighboring countries. 27,28 In adjusted regression models, fish and plant proteins were now associated with rural setting and lower SES. 1,2 The observed decline in fish was countered by an increase in consumption of chicken, eggs, and dairy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The observed decline in fish was countered by an increase in consumption of chicken, eggs, and dairy. [27][28][29] The shift in eating habits has been attributed in past studies to the "compressed modernization" of SE Asia 30 and may be linked to the growth of fast foods, which has had a decisive and documented impact on Malaysian food consumption patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The unsatisfactory intake of lycopene may be due to the different dietary eating patterns driven by the cultural boundaries. Reported findings from the Malaysian Adults Nutrition Survey (MANS) showed that white rice, marine fish, green leafy vegetables, bread, biscuits and traditional delicacies are the routine food items among the tested populations [13]. Lycopene is a red pigment found predominantly in fruits and vegetables notably tomatoes, pink guava and grapefruits, and tomato-derived products, not limited to spaghetti, pizza, tomato juice, tomato sauce and minestrone soup.…”
Section: Discussionmentioning
confidence: 99%